The effect of intraoperative antiemetics on postoperative nausea and vomiting in patients receiving intrathecal morphine for elective caesarean deliveries - Marcelo Epsztein Kanczuk; Nicholas J Lightfoot; Yayoi Ohashi; Jian Yang Chong; Hamish S Mace; David W Hoppe; Edmond J O’Loughlin (Clinical and Experimental Obstetrics & Gynecology)
Background: The incidence of postoperative nausea and vomiting (PONV) when intrathecal morphine (ITM) is used for caesarean delivery (CD) is up to 80% without antiemetic prophylaxis. Prophylactic antiemetics can reduce this rate by 50%, except for dexamethasone that did not show to be effective in this context. Combinations showed divergent results. We investigated the incidence of PONV when different combinations of antiemetics were used for CD in parturients receiving ITM. Methods: Retrospective, single centre cohort study of patients undergoing elective CD with ITM between January 2016 and October 2017. The primary outcome was the incidence of PONV requiring treatment in the first 24 hours following CD. Interactions were sought using multivariate modelling for predictors of PONV following surgery. Results: Overall, 598 women were included in the study. The rate of PONV requiring treatment was 29.1%. The rate of PONV decreased with increasing numbers of prophylactic medications (p < 0.001). Women who did not experience PONV received a greater number of antiemetics in the operating room (p < 0.001). There was a dose response relationship between ITM dose and PONV rate (p < 0.001). Dexamethasone, either alone or in combination with other agents was not protective against PONV when compared with other drug combinations (p = 0.08). Conclusions: We have demonstrated an inverse relationship between the number of prophylactic antiemetics given and the rates of PONV after caesarean delivery in the context of intrathecal morphine use. Dexamethasone use, either alone or in conjunction with other drugs did not offer advantages over other combinations where dexamethasone was avoided.